2022
DOI: 10.1007/s11060-022-04139-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging changes in patients with glioma-associated seizures

Abstract: Introduction Structural white matter changes associated with certain epilepsy subtypes have been demonstrated using diffusion tensor imaging (DTI). This observational study aims to identify potential water diffusion abnormalities in glioma patients with associated seizures. Methods Two cohorts from two centers were analyzed independently: (A) Prospectively recruited patients diagnosed with glioma who received preoperative DTI to measure mean diffusivity (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Vasogenic brain edema increases capillary permeability and broken blood–brain barrier, leading to an abnormal distribution of ions inside and outside the cells, which in turn stimulates nerves and triggers seizures ( 38 ). In addition, when astrocytes are involved in cytotoxic brain edema due to increased occupancy effects, their ability to take up glutamate is reduced, which in turn affects the stability of the nerve cell membrane, inducing neuroexcitability and ultimately leading to seizures ( 39 ). This study also found that intratumoral hemorrhage is an independent risk factor for gliomas complicated by seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Vasogenic brain edema increases capillary permeability and broken blood–brain barrier, leading to an abnormal distribution of ions inside and outside the cells, which in turn stimulates nerves and triggers seizures ( 38 ). In addition, when astrocytes are involved in cytotoxic brain edema due to increased occupancy effects, their ability to take up glutamate is reduced, which in turn affects the stability of the nerve cell membrane, inducing neuroexcitability and ultimately leading to seizures ( 39 ). This study also found that intratumoral hemorrhage is an independent risk factor for gliomas complicated by seizures.…”
Section: Discussionmentioning
confidence: 99%